Pengaruh pembebasan pajak UMKM terhadap kinerja usaha pada UMKM Kelurahan Tlogomas Kota Malang di masa Pandemi Covid-19 - Risnaningsih, Risnaningsih; Suhendri, Hendrik; Selan, Nuni Rosmiati (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
This study was conducted to examine the effect of the MSME tax exemption on business performance during the COVID-19 pandemic in MSMEs in the Tlogomas village. The sampling technique using the Slovin formula was obtained a minimum sample of 32 respondents. Data analysis technique using simple linear regression test. The results showed that the MSME tax exemption had a positive and significant impact on business performance during the covid-19 pandemic.